The immediate effect of a gentle heel strike on peroneal muscle prelanding activation during prolonged treadmill running in males - Shen, W.; White, M. W.; Fong, D. (ISBS Proceedings Archive (Michigan), 2022)
Ankle sprains are common in runners. Inactive peroneal longus (PL) is one of the main contributors. The aim of this project was to study the immediate effect of running with a gentle heel strike (GHS) on pre-landing activation of the PL. It was hypothesised that GHS would pre-activate the PL to a greater extent. 11 healthy participants partook in two separate trials. The first involved running on a force plate treadmill with normally, the second with ~70% of mean heel pressure (MHP). GHS showed higher pre-landing PL activated level. There was data showing significant differences between groups at multiple timepoints. The present study showed that running with ~70% MHP compared with 100% increased PL activation for pre-landing phases. Further study should be implemented to see the fatigue level of PL during pro-longed running when running gently.